KONTRIBUSI MOTIVASI BELAJAR DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN TEKNIK VIDEO KELAS XI SMK 5 PADANG - Desri Fagia Nonik; Nurindah Dwiyani; Dedy Irfan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This research was motivated by the problem of low learning achievement in the subjects of video techniques class XI student majoring in audio video engineering at SMK Negeri 5 Padang , where 40.54 % of students gain mastery of learning outcomes under Kriteria Ketuntasan Minimal ( KKM ) . KKM set the school on subjects a video engineering of 75 with a range of values ​​0-100 . The purpose of this study was to reveal the contribution of learning motivation and discipline to learn the subjects learning outcomes of students majoring in video engineering video audio engineering at SMK Negeri 5 Padang . This research is descriptive nature of correlation . The population in this study were all students of class XI Audio Video Engineering Department SMK Negeri 5 Padang , consists of three classes totaling 74 people , and the sample amounted to 43 people . Technique of random sampling ( Simple random sampling ) . Student learning outcomes data obtained from subject teachers video technique class XI SMK Negeri 5 Padang in 2012 . While the motivation to learn and the discipline of data collected through a questionnaire study using a Likert scale that has been tested for validity and reliability . Data were analyzed using statistical methods with the help of Microsoft Excel 2007 software . The results of data analysis showed : ( 1 ) learning motivation accounted for 13.06 % of the learning outcomes of students of SMK Negeri 5 Padang , ( 2 ) learn discipline contributes 10.75 % to the learning outcomes of students of SMK Negeri 5 Padang ; ( 3 ) learning motivation and discipline to learn together accounted for 19.45 % of the learning outcomes of students of SMK Negeri 5 Padang . So it can be concluded that the motivation to learn and the discipline of learning contribute to learning outcomes , the higher the students' motivation in the learning process and the higher discipline of learning , then learning outcomes will be higher . Keywords :     Motivation Learning, Discipline Learning , Learning Outcomes , Descriptive Correlation , Simple Random Sampling